Supersensitivity of the isolated guinea-pig vas deferens induced by a toxic fraction of scorpion venom (Tityus serrulatus) - Melito, I.; Prado, W. A.; Corrado, A. P.; Coutinho Netto, J. (Elsevier, 1984)
1. Tityustoxin (TsTx), a toxic fraction of Tityus serrulatus venom, was studied on the isolated guinea-pig vas deferens. It increased significantly the maximal response of the preparation to both norepinephrine and acetylcholine and decreased the effective median dose of norepinephrine. 2. The effect of TsTx on norepinephrine median dose was unchanged when atropinized or pharmacologically 'denervated' preparations were used but was abolished when both procedures were associated. 3. Atropinization of pharmacologically denervated muscles almost never modify the TsTx-induced increase in the maximal response to norepinephrine. 4. On denervated or phentolamine-treated muscles TsTx-induced increase in the maximal response to acetylcholine was abolished. 5. It was concluded that toxin predominantly induces adrenergic postsynaptic supersensitivity. 6. Of minor significance, it also induces presynaptic cholinergic and adrenergic supersensitivity. 7. Comparison of these results with those of crude venom indicates that TsTx effects may result from the sum of the effects of subcomponents not demonstrated by the chemical procedures here utilized.
Keywords: acetylcholine; atropine; metirosine; noradrenalin; phentolamine; postsynaptic receptor; reserpine; scorpion venom; tityus toxin; animal cell; arthropod; autonomic nervous system; guinea pig; male genital system; nonhuman; supersensitivity; vas deferens; Acetylcholine; alpha-Methyltyrosine; Animal; Atropine; Guinea Pigs; In Vitro; Male; Methyltyrosines; Muscle, Smooth; Neurotoxins; Norepinephrine; Phentolamine; Receptors, Adrenergic; Receptors, Cholinergic; Scorpion Venoms; Vas Deferens